Світові тенденції ринку вторинної переробки відходів і брухту міді (аналітичний огляд) - Гнатуш, В.А. (Physico-technological Institute of Metals and Alloys, 2024)
Recycling of waste and scrap metal is an important component of the modern economy, because natural metal resources are exhaustible. And since copper waste and scrap can be considered as renewable resources, the analysis of the world market for secondary processing of copper waste and scrap is relevant in the 21st century. It is shown that copper is used in many industries. The largest consumers of this product are mechanical engineering (32 % share) and construction (26 %). In the 21st century (2001-2022), the global production of refined copper increased from 15.6 to 25.7 million tons (CAGR 2.3 %), and its use — from 14.9 to 26.1 million tons (CAGR 2.6 %). By the end of 2022 the leaders in the production of refined copper in the world were China (share 43 %), Chile (8 %), the Republic of Congo (7 %) and Japan (6 %). Analytics show that the average level of copper scrap recycling in the world at the end of the useful life is about 45 %. If the recycling rate reaches 60 % by 2035, then the estimated total volume of copper scrap will reach 14 million tons by 2030, and 25 million tons by 2050. At the same time, a market for copper waste and scrap has formed in the world. In quantitative terms the world export of the specified goods in the years 2003-2022 varied from 3.8 million tons (2003) to 6.8 million tons (2013). In subsequent years, exports were characterized by a certain stability and fluctuated in the range of 5...6 million tons. The main exporters of these goods in 2022 were the USA (16.4 % share), Germany (7.2 %) and Japan (6.9 %), and the importers were China (37.1 %), Germany (10.4 %) and Republic of Korea (7.5 %). Information on the leading copper scrap processing companies in the world and the USA is considered. Information on the technological aspects of copper scrap processing is presented. It is shown that the processing industry has at its disposal direct and indirect methods of sorting, a line of equipment for metallurgical processing of copper scrap. Certain companies are found to use computerized systems to determine thermal characteristics, cost and the most efficient method of remelting, including the need to use multiple types of scrap. Information is provided regarding company Continuus-Properzi S.p.A. (Italy), which uses three technology options for copper scrap processing. It is noted that the available equipment allows processing companies to create a technological cycle of processing with optimal efficiency depending on the quality of incoming scrap. Information is presented on the state of the Ukrainian market for copper waste and scrap, refined copper and copper products, as well as domestic technological developments.